Human Lung Fibroblasts Exhibit Induced Inflammation Memory via Increased IL6 Gene Expression and Release - Yap, Jennifer Maries Go; Ueda, Takashi; Kanemitsu, Yoshihiro; Takeda, Norihisa; Fukumitsu, Kensuke; Fukuda, Satoshi; Uemura, Takehiro; Tajiri, Tomoko; Ohkubo, Hirotsugu; Maeno, Ken; Ito, Yutaka; Oguri, Testsuya; et al. (Frontiers in Immunology, 2022)
Fibroblasts of different origins are known to possess stromal memory after inflammatory episodes. However, there are no studies exploring human lung fibroblasts memory which may predict subsequent inflammatory response in chronic respiratory diseases and COVID-19. MRC-5 and HF19 human lung fibroblasts cell lines were treated using different primary and secondary stimulus combinations: TNFα-WD-TNFα, Poly (I:C)-WD-TNFα, TNFα-WD-Poly (I:C), or LPS-WD-TNFα with a 24 hrs rest period (withdrawal period; WD) between the two 24 hrs stimulations. TLR3 and NF-κB inhibitors were used to determine pathways involved. Effect of SARS-Cov-2 spike protein to inflammatory response of lung fibroblasts was also investigated. mRNA expressions of genes and IL6 release were measured using qRT-PCR and ELISA, respectively. Statistical significance was determined by using one- or two-way ANOVA, followed by Bonferroni’s post hoc analysis for comparison of multiple groups. Pre-exposure with Poly (I:C) significantly increased TNFα-induced IL6 gene expression and IL6 release in both cell lines. While it did neither affect gene expression of IL1B, IL2, IL8 and MMP8, nor fibrosis-related genes: ACTA2, COL1A1, POSTN, and TGFB1. Inhibition of TLR3 or NF-κB during primary stimulation significantly downregulated IL6 release. Simultaneous treatment of MRC-5 cells with SARS-CoV-2 spike protein further increased TNFα-induced IL6 release however pre-exposure to Poly (I:C) did not affect it. Human lung fibroblasts are capable of retaining inflammatory memory and showed an augmented response upon secondary exposure. These results may contribute to the possibility of training human lung fibroblasts to respond suitably on inflammatory episodes after viral infection.